Type XVII collagen: Relevance of distinct epitopes, complement-independent effects, and association with neurological disorders in pemphigoid disorders - Opelka, Bianca; Schmidt, Enno; Goletz, Stephanie (Frontiers in Immunology, 2022)
Pemphigoid diseases (PD) are autoimmune skin blistering diseases characterized by autoantibodies directed against proteins of the cutaneous basement membrane zone (BMZ). One of the major antigens is type XVII collagen (BP180), a transmembrane glycoprotein, which is targeted in four PDs, bullous pemphigoid, mucous membrane pemphigoid, linear IgA dermatosis, and pemphigoid gestationis. To date, different epitopes on BP180 have been described to be recognized by PD disease patients’ autoantibodies. Different BP180 epitopes were associated with distinct clinical phenotypes while the underlying mechanisms are not yet fully understood. So far, the main effects of anti-BP180 reactivity are mediated by Fcγ-receptors on immune cells. More precisely, the autoantibody-antigen interaction leads to activation of complement at the BMZ and infiltration of immune cells into the upper dermis and, by the release of specific enzymes and reactive oxygen species, to the degradation of BP180 and other BMZ components, finally manifesting as blisters and erosions. On the other hand, inflammatory responses independent of Fcγ-receptors have also been reported including the release of proinflammatory cytokines and internalization and depletion of BP180. Autoantibodies against BP180 can also be found in patients with neurological diseases. The assumption that the clinical expression of PD depends on epitope specificity in addition to target antigens, autoantibody isotypes, and antibody glycolization is supported by the observation that epitopes of PD patients differ from those in patients with PD. The aim of the present review is to describe the fine specificities of anti-BP180 autoantibodies in different PD and highlight the associated clinical differences. Furthermore, the direct effects after binding of the autoantibodies to their target are summarized.